2018
DOI: 10.1589/jpts.30.282
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increased functional residual capacity on the active range of thoracic axial rotation in healthy young men

Abstract: [Purpose] To understand the effect of increased functional residual capacity (FRC) on the active range of thoracic axial rotation (AROTAR) in healthy young men. [Subjects and Methods] Thirty-nine right-handed healthy male volunteers (age=20.1 ± 1.6 years) participated in this study. A standard plastic goniometer was used to measure the AROTAR in the supine position with both glenohumeral joints fully flexed. AROTAR was recorded at the resting expiration level (REL) and for 4 different FRC levels: 500, 1,000, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The change in FFD also depended on the amount of inhaled air. An expansion of the thorax with an increase in the FRC led to decreased mobility of trunk rotation as per our previous study2, 4 ) . In this study, we could demonstrate decreased active trunk flexion with a quantitative increase in FRC, in addition to trunk rotation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The change in FFD also depended on the amount of inhaled air. An expansion of the thorax with an increase in the FRC led to decreased mobility of trunk rotation as per our previous study2, 4 ) . In this study, we could demonstrate decreased active trunk flexion with a quantitative increase in FRC, in addition to trunk rotation.…”
Section: Discussionsupporting
confidence: 79%
“…Our previous study2 ) demonstrate that an increase in FRC might decrease an active range of thoracic axial rotation in healthy young participants. The causes and mechanisms for poor thoracic mobility in these patients are complicated.…”
Section: Introductionmentioning
confidence: 90%
“…Our previous study demonstrated that increased functional residual capacity might decrease the active range of thoracic axial rotation 5) and a finger-floor distance 6) in healthy young adults, though the causes and mechanisms of poor thoracic mo-bility in patients with COPD are complicated. These studies had limitations that required solving, i.e., IC was not measured using spirometry.…”
Section: Introductionmentioning
confidence: 99%